UJI EFEKTIFITAS LARUTAN PESTISIDA NABATI RIMPANG LENGKUAS, DAUN SERAI, DAN DAUN BABADOTAN PADA PENGENDALIAN HAMA PENGHISAP BUAH (Helopeltis sp.) TANAMAN KAKAO - Dewi Hastuti; Rusmana .; Puad Hasan (Jurnal Agroekoteknologi, 2015)
The objective of the research was to determine the effectiveness of botanical pesticides Galangal rhizome, Lemongrass, and Babadotan leaves solvent on mosquito bugs (Helopeltis sp) of Cocoa crop (Theobroma cacao L.). The research was conducted from July to August 2013 on cocoa farms at Luarang Sukalaba Village, Gunungsari District, Serang Regency of Banten Province. The research used a randomized block design (RBD) with one factor that consists of 4 treatments, ie P0 = Control, PL = Galangal Rhizome 100 gr/l, PB = Babadotan Leaves 100 gr/l, PS = Leaves Lemongrass100 gr/l and these were repeated four times. The parameters observed were widespread attack, intensity of pest attacks and Helopeltis sp population. The results showed that application of Galangal Rhizome solvent could suppress extensive solution and intensity of Helopeltis pest attacks. The application of lemongrass leaves solvent solution could suppress the pest population, where as babadotan leaves act as an attractant against Helopeltis sp. in cocoa.Key Words: Botanical pestisides, Insect pest, Galangal rhizome, Lemongrass, and Babadotan